الحركة المتجانسة في نموذج بيانكي من النوع الخامس في هندسة ليرا - الصباغ, ف; عبد البصير, ف; مصطفى, ح (مجلة العلوم الطبيعية و الحياتية والتطبيقية, 2017)
In this paper we study a homothetic vector field of a Bianchi type-V model based on Lyra geometry. The aim of this paper is to get the components of  homothetic vector field  in Lyra geometry for Bianchi type-V, compare between it and the case of  Bianchi type-I. Using ordinary method and Computer program to get the components of  the vector . The results are compatible in the two methods and get the condition that the results  tends to the case of  Bianchi type-I.  The cases when a displacement vector is a function of  t and when it is constant are considered. In both two cases we investigate the equation of state.
Keywords: نوع بيانكي الخامس; حقل متجه متجانس; هندسة ليرا; رموز كريستوفال; هندسة ريمان